DOI: 10.26686/wgtn.17134136.v1
|View full text |Cite
|
Sign up to set email alerts
|

A gendered difference? Female experience of drug and alcohol treatment in New Zealand

Abstract: <p>This study examined women’s experiences of drug and alcohol treatment in New Zealand, with a focus on Methadone Maintenance Treatment (MMT). The qualitative literature on the treatment experiences of substance-using women is scarce, especially in a New Zealand context, with the majority of literature being quantitative, male-focused, and lacking the female voice. Available literature suggests that substance-using women have unique needs and experiences which must be addressed and acknowledged in treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(28 citation statements)
references
References 84 publications
0
27
0
Order By: Relevance
“…In contrast, most women in Conroy's (2018) research did not report experiencing stigma, but, for those who did, it significantly impacted their lives. Examples of stigma included being falsely accused of drug seeking or child abuse by hospital staff, leading to being reported to child protection services (Conroy, 2018).…”
Section: Experiences Of Healthcare Providers and Aod Servicesmentioning
confidence: 69%
See 4 more Smart Citations
“…In contrast, most women in Conroy's (2018) research did not report experiencing stigma, but, for those who did, it significantly impacted their lives. Examples of stigma included being falsely accused of drug seeking or child abuse by hospital staff, leading to being reported to child protection services (Conroy, 2018).…”
Section: Experiences Of Healthcare Providers and Aod Servicesmentioning
confidence: 69%
“…Strengths and weaknesses within AOD services. Conroy (2018) stated that an unexpected finding was that participants in her study reported generally positive experiences of AOD treatment in Aotearoa.…”
Section: Original Articlementioning
confidence: 93%
See 3 more Smart Citations